ULTRASOUND IMAGING OF THE SPLEEN, STOMACH, LIVER, KIDNEYS, BLADDER, AND PROSTATE IN PIGLETS (Sus scrofa domestica) - Gunanti, Gunanti; Khairunnisa, Carina; Annisa, Fadhilah Nur; Retnani, Elok Budi; Amin, Akhmad Arif; Rahmiati, Dwi Utari (Jurnal Kedokteran Hewan, 2021)
This study aims to describe ultrasonographic imaging of the spleen, stomach, liver, kidney, bladder, and prostate in piglets (Sus scrofa domestica). Ultrasonography was performed on six male piglets aged 1 month with a body weight of 4-8 kg. Ultrasonography of the spleen, stomach, liver, urinary bladder, and prostate was observed in the dorsal-recumbency position, and the kidney was observed in the lateral-recumbency position. The ultrasound examination used the Chison EBit 60, which is a linear type transducer with a frequency of 9 MHz, transverse and sagittal positions, and a gain of about 55-80. Ultrasonography of the spleen showed that the shape of the spleen head varied in each individual. The results of gastric ultrasonography showed the gastric lining clearly and the similarity of the position, shape, structure, echogenicity, and size of the stomach. The results of liver ultrasonography showed that the echogenicity of the liver tended to be hyperechoic, the kidneys were hyperechoic, and the bladder was hypoechoic due to the use of improper gain. The average length of the right kidney was 4.730.50 cm and the left kidney was 4.080.26 cm. The bladder wall thickness was 1.30.31 mm. Imaging of the bladder showed changes in wall size and echogenicity. Prostate ultrasound results obtained an average length of 2.680.45 cm, width 1.690.35 cm. The results of this study can be used as a reference for normal data on organ position, organ structure, and organ echogenicity of the spleen, stomach, liver, kidney, bladder, and prostate in piglets.